Groundwater and indoor air quality of urban village housing: study in Janturan, Warungboto, Yogyakarta - Mahfudh, Nurkhasanah; Prasasti, Dian; Ananda, Anugrah Tri; Rahmawati, Frida; Sulistyawati, Sulistyawati; Muchlis, Muchlis; Murtyas, Solli Dwi; Hagishima, Aya (International Journal of Public Health Science (IJPHS), 2024)
Water and air are important elements for life. The presence of pathogenic bacteria in the surrounding environment can cause health problems resulting from the low quality of water and air. The purpose of this study is to measure the quality of groundwater and air based on microbiological parameters in urban village housing. This research was conducted in a descriptive survey, and a purposive sampling technique was carried out. Groundwater and air samples were taken from six residents' houses located in the Janturan area. The water quality test used the most probable number (MPN) method and the air quality test used the agar filter method using a microbiological air sampler (MAS) to trap microbes. The results of the MPN test for total coliform bacteria from six samples of groundwater showed that three samples were positive for coliform bacteria which exceeded the threshold according to Indonesian standard<50 MPN/100 ml. Assay of E. coli bacteria showed that all samples of groundwater positively contained E. coli bacteria which exceeded the threshold of 0 MPN/100 ml. The results of indoor air quality measurements from 6 residents' houses showed that five houses have air quality did not meet the standard for indoor air germ numbers based on Indonesian standard, less than 700 CFU/m3 (colony forming units per metres cubic) and 1 house that got the number of airborne germs, in the normal range, namely 356 CFU/m3. It was concluded that the water quality and air quality in the urban village did not meet health requirements.